ANALISIS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KURIKU-LUM 2013 BAGI ANAK BERKEBUTUHAN KHUSUS DI SDLB 01 REJANG LEBONG - Zahratul Fitria; Sukiman Sukiman; M Zaidul Kirom (caXra: Jurnal Pendidikan Sekolah Dasar, 2022)
Abstract:The purpose of the study to analyze a curriculum that is currently used is the 2013 curriculum in Islamic religious education materials where this study focuses on children who have special needs. The research method used in this study is descriptive qualitative research which is conducted at SDLB 01 Rejang Lebong, one educator who as a subject, data collection techniques with interviews, observations and data analysis. The result of this research is that a special curriculum is needed for the subjects of Islamic religious education of children with special needs and there must be simplification in the material and evaluation which in this case must be in accordance with the characteristics of children with special needs in the application of learning models used classical class and one on one class models. Educators in informing learners are certainly needed a patience and varied learning methods can make learners not bored in learning. Keywords: Islamic Religious Learning, Curriculum 2013, Children with Special Needs.